2008
DOI: 10.1016/j.cmpb.2007.11.019
|View full text |Cite
|
Sign up to set email alerts
|

A computer-assisted data collection system for use in a multicenter study of American Indians and Alaska Natives: SCAPES

Abstract: We describe a computer-assisted data collection system developed for a multicenter cohort study of American Indian and Alaska Native people. The study computer-assisted participant evaluation system or SCAPES is built around a central database server that controls a small private network with touch screen workstations. SCAPES encompasses the self-administered questionnaires, the keyboard-based stations for interviewer-administered questionnaires, a system for inputting medical measurements, and administrative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The ACASI format has been shown to provide consistent results with the paper-and-pencil (PAPI) version of the instruments 46,47 and to be acceptable to a low-income population. [48][49][50][51] The ACASI program used in this project was developed by the author using QDS version 2.5. 52 Permission to use the ADDQoL in ACASI format could not be obtained from the owner, so the PAPI format was used instead.…”
Section: Methodsmentioning
confidence: 99%
“…The ACASI format has been shown to provide consistent results with the paper-and-pencil (PAPI) version of the instruments 46,47 and to be acceptable to a low-income population. [48][49][50][51] The ACASI program used in this project was developed by the author using QDS version 2.5. 52 Permission to use the ADDQoL in ACASI format could not be obtained from the owner, so the PAPI format was used instead.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed methods have been described elsewhere (Edwards et al, 2007; Slattery et al, 2007, 2008; Edwards et al, 2008). Briefly, Navajo EARTH study participants are 18 years of age or older, self-identify as American Indian or Alaska Native, have given informed consent, understand English or Navajo, and are eligible to receive care at the Indian Health Service.…”
Section: Methodsmentioning
confidence: 99%
“…The EARTH study collected similar self-reported data using audio computer-assisted self-interview methods [33,34]. Demographic data obtained by all studies included age, sex and education level in years of school completed.…”
Section: Methodsmentioning
confidence: 99%